Decomposition Of Li2CO3 In Existence Of SiO2 In Mould Flux Of Steel Casting - J. -W. Kim; Y. -B. Kang; H. -G. Lee (The Southern African Institute of Mining and Metallurgy, 2004)
The effect of SiO2addition on the decomposition of Li2CO3was investigated at temperatures up to 1000ºC. It was found that addition of SiO2greatly enhanced the decomposition of Li2CO3. The main decomposition reaction started at around 600ºC, and completed just above the melting point of Li2CO3. The major decomposition product was Li2O?SiO2irrespective of the Li2CO3to SiO2mixing ratio while both reactants were available. It was ascertained that a liquid layer betweenLi2CO3and SiO2particles formed and facilitated the decomposition reaction. The governing reaction of the decomposition was the one between the dissolved Li2CO3and SiO2in the liquid layer to form Li2O?SiO2. The decomposition rate was independent of the Li2CO3/SiO2mixingratio until either one had been completely exhausted. When excess Li2CO3existed, it further reacted with the initial product of Li2O?SiO2to form 2Li2O?SiO2. When SiO2was found in excess, on the other hand, no further reaction took place. This is attributed to the fact that uponLi2CO3exhaustion there is no liquid phase available to facilitate further reaction. The apparent activation energy of the decomposition of Li2CO3in existence with SiO2is 198 kJ mol-1.